2015
DOI: 10.1155/2015/918361
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Ameliorate CLP‐Induced Rat Intestinal Injury via Inhibition of Inflammation

Abstract: The aim was to verify that dexmedetomidine (DEX) can attenuate CLP-induced intestinal injury via inhibition of inflammation. Male Sprague-Dawley (SD) rats were randomly allocated into Sham group and the other three CLP model groups, in terms of different treatments: placebo, DEX, and yohimbine plus DEX (DEX + YOH) groups. Pathology examination was conducted with HE stain. To identify differences among groups, the levels of DAO, and D-lactate in serum were measured by spectrophotometry, and the levels of TNF-α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…As a widely used anesthetic adjuvant in clinical setting, dexmedetomidine has a high affinity for the α 2 -adrenoceptor and is approved for sedation in critically ill patients, due to its sedative effects without respiratory depression [6]. Many studies also showed the anti-inflammatory effect of dexmedetomidine by reducing the levels of inflammatory cytokines in some specific cases [7,23,24]. Based on previous research [9], we set the dose of dexmedetomidine at 1 µg/kg/hour which is the equivalent of the clinical dose in humans.…”
Section: Discussionmentioning
confidence: 99%
“…As a widely used anesthetic adjuvant in clinical setting, dexmedetomidine has a high affinity for the α 2 -adrenoceptor and is approved for sedation in critically ill patients, due to its sedative effects without respiratory depression [6]. Many studies also showed the anti-inflammatory effect of dexmedetomidine by reducing the levels of inflammatory cytokines in some specific cases [7,23,24]. Based on previous research [9], we set the dose of dexmedetomidine at 1 µg/kg/hour which is the equivalent of the clinical dose in humans.…”
Section: Discussionmentioning
confidence: 99%
“…27 There is increasing evidence that DEX has organ protective properties in several injury models including ischaemiareperfusion, inflammation, and traumatic brain injury. [28][29][30][31][32] More recently, DEX has been shown to be protective against neurotoxicity induced by ketamine and isoflurane in a neonatal rat model. 33 34 Sevoflurane (SEVO) is the preferred and most frequently used volatile anaesthetic in paediatric anaesthesia.…”
mentioning
confidence: 99%
“…Dexmedetomidine also may provide anti-inflammatory benefits in response to surgical stress through cytokine inhibition and suppression of adrenoceptor-mediated vascular constriction in the renal structures. 7,8 These effects perhaps explain the Peng et al findings of reduced AKI with dexmedetomidine use, specifically in the preoperative and intraoperative settings, irrespective of postoperative use. With the temporal insult of cardiopulmonary bypass, early preservation of the renal vasculature may serve as a mechanism for prevention of phenotypic AKI in the post-bypass setting.…”
mentioning
confidence: 95%
“…A similar hypothesis has been proposed for early prophylactic dexmedetomidine application in sepsis to protect against intestinal injury. 7,8 The Peng et al study is not without limitation. The 9 studies included in the analysis spanned nearly a decade, and therefore several different definitions were used to characterize AKI.…”
mentioning
confidence: 97%